2010
DOI: 10.2353/ajpath.2010.090158
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinases 3 Regulates Resolution of Inflammation following Acute Lung Injury

Abstract: Tissue inhibitor of metalloproteinases 3 (TIMP3) inhibits not only matrix metalloproteinases but also a disintegrin and metalloproteinase domain family members and thus contributes to controlling diverse processes mediated by proteolysis. We used Timp3(-/-) mice to assess the role of this inhibitor in acute lung injury. After bleomycin-induced injury, inflammation, as indicated by the influx of neutrophils in bronchoalveolar lavage (BAL), peaked at 7 days post-injury in the wild-type mice and began to wane the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 38 publications
2
72
0
Order By: Relevance
“…Recently, we demonstrated that the absence of TIMP-3 resulted in increased neutrophil accumulation in the lungs after bleomycin-induced lung injury, ultimately leading to an impaired resolution of inflammation (23). In this study, we confirm the role of TIMP-3 in regulating inflammation after lung injury, and identify TIMP-3 as a key moderator of macrophage proinflammatory (M1) polarization.…”
supporting
confidence: 73%
“…Recently, we demonstrated that the absence of TIMP-3 resulted in increased neutrophil accumulation in the lungs after bleomycin-induced lung injury, ultimately leading to an impaired resolution of inflammation (23). In this study, we confirm the role of TIMP-3 in regulating inflammation after lung injury, and identify TIMP-3 as a key moderator of macrophage proinflammatory (M1) polarization.…”
supporting
confidence: 73%
“…23 Loss of TIMPs would be expected to lead to enhanced matrix proteolysis; however, TIMP3 knockout mice demonstrated enhanced fibrosis after bleomycin associated with persistent neutrophil influx. 27 Mice lacking TIMP1 have similar severity of fibrosis but greater neutrophilic inflammation compared with wild-type mice after bleomycin injury. 28 These studies and others now demonstrate that the MMPs and TIMPs influence several cellular processes, including proliferation, survival, and inflammation, that directly or indirectly influence myofibroblast activation and ECM turnover.…”
Section: Composition Of the Extracellular Matrix In Fibrosismentioning
confidence: 98%
“…, and Sdc1 2/2 mice (all C57Bl/6; near equal mix of females and males; 8 weeks old) were intubated with 2 3 10 9 CFU live Pseudomonas aeruginosa (PAO1) or bleomycin (4 U/kg), as previously described (12,13). Mice were killed at the indicated times, and lungs were either lavaged twice with PBS (1 ml/lavage) or infused with optical cutting temperature compound (VWR, Batavia, IL).…”
Section: /2mentioning
confidence: 99%